High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272